2019
DOI: 10.1186/s12889-019-7443-4
|View full text |Cite
|
Sign up to set email alerts
|

Infant, neonatal, and postneonatal mortality trends in a disaster region and in Japan, 2002–2012: a multi-attribute compositional study

Abstract: Background The reductions achieved in infant mortality in Japan are globally regarded as remarkable. However, no studies in Japan have classified infant mortality trends into neonatal and postneonatal or considered regional issues. This study aimed to explore trends in neonatal and postneonatal deaths, both overall for Japan and in a region affected by a natural disaster. Methods Drawing on national infant death data, we used a multi-attribute compositional study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In conclusion, the importance of this research is highlighted, since knowing the distribution of causes of death and risk factors in each place, as well as the socio-demographic aspects that influence them, corroborates a more comprehensive and consolidated understanding of these data, implementing policies aimed at combating inequalities in infant mortality, as well as providing valuable information to improve child health indicators (Dandona et al, 2020;Tashiro et al, 2019).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In conclusion, the importance of this research is highlighted, since knowing the distribution of causes of death and risk factors in each place, as well as the socio-demographic aspects that influence them, corroborates a more comprehensive and consolidated understanding of these data, implementing policies aimed at combating inequalities in infant mortality, as well as providing valuable information to improve child health indicators (Dandona et al, 2020;Tashiro et al, 2019).…”
Section: Discussionmentioning
confidence: 61%
“…In the national scenario, the absence of a partner, maternal age ≥ 35 years, male gender, multiple gestation, inadequate and absent prenatal care, presence of intercurrences during pregnancy, congenital malformation, Apgar< 7 in the fifth minute, low and very low birth weight, gestational age ≤ 37 weeks, and cesarean delivery are presented as risk factors for neonatal mortality (Veloso et al, 2019). In Japan, in which the top five causes of death for neonates were congenital hypoplasia, trisomy, low birth weight, and severe neonatal asphyxia (Tashiro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Between 2002 and 2012, 31,012 babies died in Japan and 1450 in Tohoku. The Great East Japan Earthquake and Tsunami (GEJET) appears to have a greater impact on post neonatal deaths than neonatal deaths (Toshiro et al, 2019). Toshiro et al (2018) examined the deaths of children under the age of 10 years after 2008-2014 and after the 2011 great earthquake in Japan, and it was found that the mortality rate among children younger than 10 years old was 6.4 times higher than the rate before and after 2011 during the 2011 disaster period.…”
Section: Infant-childmentioning
confidence: 99%
“…In recent years, several countries have shown a significant drop in infant and child morbidity and mortality rates (Dandona et al, 2020;Burstein et al, 2019;UNICEF, 2018;UNICEF, 2019). However, despite the advances in the protection of children's health on the world stage, research shows that mortality in this group is still high and its profile significantly influenced by socio-demographic inequalities (UNICEF, 2018;Tashiro et al, 2019). It is recorded that 58% of infant deaths that occurred between 2000 and 2017 could have been prevented in the absence of these differences (Burstein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%